Utilization of coarse non-ferrous fraction of incineration bottom ash as aerating agent in autoclaved aerated concrete - Liu, Yiquan (2023)
Past studies by the authors have demonstrated the feasibility of utilizing municipal solid waste (MSW) incineration bottom ash (IBA) as an aerating agent to produce autoclaved aerated concrete (AAC). However, the gas generation potential of as-received IBA (General IBA) is significantly poorer than conventional aerating agents such as pure aluminum powder. The classification of IBA showed that coarse non-ferrous IBA fraction with particle size greater than 1.18 mm (CNF-IBA) contains a higher concentration of metallic aluminum. This study proposes specifically utilizing CNF- IBA fraction as an aerating agent to produce AAC. Two other AACs with pure Al powder and General IBA as aerating agents were investigated for systematic comparison. The aeration kinetics, fresh, and hardened properties were experimentally investigated. A novel approach is presented to study the influence of coordination between aeration extent and yield stress development on volume expansion capacity. The developed AAC with CNF-IBA exhibited the highest specific compressive strength. The leaching analysis showed that the usage of IBA as an aerating agent in AAC production is safe during the service life of AAC, and its demolished samples at the end of service time can be landfilled as inert material.